Saint Vincent and the Grenadines. Significant achievements 2012 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Saint Vincent and the Grenadines during 2012 are identified, with respect to the needs and interests of the country, strengthening issues such as financing, animal health, rural development, sanitation, poultry farming, biotechnology, competitiveness, agribusiness, trade and inclusion of women in agriculture. Finally, technical support was provided to improve vegetable value chains, animal disease control, and pest control, such as black sigatoka.